2008
DOI: 10.1002/anie.200801120
|View full text |Cite
|
Sign up to set email alerts
|

Simple NUF3 and PUF3 Molecules with Triple Bonds to Uranium

Abstract: The chemical behavior of actinide elements must be understood to manage effectively the many uses of actinide materials in todays world. Considerable interest has developed in recent years in actinide (An) complexes with metalligand multiple bonds. Most of these investigations have centered on organometallic systems, [1] and molecular complexes containing metal nitride units have been prepared. [2][3][4][5][6] These compounds with U = N linkages and organoimido (An = NR) and phosphinidene (An = PR) groups [7,8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
125
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(135 citation statements)
references
References 46 publications
10
125
0
Order By: Relevance
“…16 The subsequent reaction of U and NF 3 produced only the most stable NUF 3 product. 17 We have published a short description of the dinitrogen complexes of NUN and UN formed upon sample annealing in recent argon matrix investigations of U and N 2 reactions. 18 The most important new information on the terminal nitride UN is the observation of rotationally resolved optical transitions of supersonically cooled UN, which provided a ground-state UN bond length of 1.7650 (12) Å.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 The subsequent reaction of U and NF 3 produced only the most stable NUF 3 product. 17 We have published a short description of the dinitrogen complexes of NUN and UN formed upon sample annealing in recent argon matrix investigations of U and N 2 reactions. 18 The most important new information on the terminal nitride UN is the observation of rotationally resolved optical transitions of supersonically cooled UN, which provided a ground-state UN bond length of 1.7650 (12) Å.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Spurred on by previous matrix isolation experiments 54,55 37,43 . From a main group perspective, these species represent fundamental, metal-stabilized parent p-block fragments that are predominantly found as transient intermediates in the gas-phase or low-temperature matrices.…”
mentioning
confidence: 97%
“…A thorium polyarsenide cluster is known 52 , but otherwise uranium-arsenic complexes are limited to computational investigations 53 or low-temperature matrix isolation experiments 54,55 . Spurred on by previous matrix isolation experiments 54,55 and the recent isolation of terminal uranium(V)-and (VI)-nitrides 38,39 , we reported that by using uranium(IV) precursors exemplified by [U(Tren TIPS )(THF)][BPh 4 ] [1, Tren TIPS = N(CH 2 CH 2 NSi i Pr 3 ) 3 ], parent uranium(IV) pnictide complexes [U(Tren TIPS )(EH 2 )] [E = N, 2a; E = P, 2b] can be accessed and converted to the corresponding uranium(IV) terminal parent imido and phosphinidene complexes [U(Tren TIPS )(EH)][K(L) 2 ] [E = N, L = 15-crown-5 ether (15C5), 3a; E = P, L = benzo-15-crown-5 ether (B15C5), 3b] 37,43 . From a main group perspective, these species represent fundamental, metal-stabilized parent p-block fragments that are predominantly found as transient intermediates in the gas-phase or low-temperature matrices.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…The isolation of terminal uranium nitride species [N"U@NH], [N"U@O] + , [N"U"N], and [N" UF 3 ] has been achieved by inert gas matrices at lower temperatures [1][2][3] [5]. A number of theoretical studies have been carried out for uranium compounds containing triple bonds between uranium and main group elements [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The calculated U"E bond distances at various level of theory are summarized in Table 1 3 ] at CASPT2 level indicate that the more electronegative substituents lengthen the U"N bond distance.…”
Section: Introductionmentioning
confidence: 99%